Parental Overcontrol and Adolescent Social Withdrawal: The Mediating Role of Fear of Evaluation - Nikolova, Mariana; Adeyemi, Ibrahim; Sharma, Neha (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the relationship between parental overcontrol and adolescent social withdrawal, with fear of negative and positive evaluation as potential mediating variables.Methods: The research employed a descriptive correlational design and included a sample of 551 Nigerian adolescents selected based on the Morgan and Krejcie table. Data were collected using standardized self-report instruments: the Psychological Control Scale–Youth Self-Report (PCS-YSR) for parental overcontrol, the Brief Fear of Negative Evaluation Scale (BFNE), the Fear of Positive Evaluation Scale (FPES), and the Withdrawn/Depressed subscale of the Youth Self-Report (YSR). Descriptive statistics and Pearson correlation coefficients were calculated using SPSS-27, and Structural Equation Modeling (SEM) was conducted via AMOS-21 to examine direct and indirect pathways among the variables.Findings: Pearson correlation analysis showed that parental overcontrol was significantly associated with fear of negative evaluation (r = .51, p < .001), fear of positive evaluation (r = .47, p < .001), and social withdrawal (r = .42, p < .001). SEM results confirmed that the structural model had good fit indices (χ² = 146.23, df = 84, χ²/df = 1.74, CFI = 0.97, RMSEA = 0.041). Parental overcontrol had significant direct effects on fear of negative evaluation (β = .51, p < .001), fear of positive evaluation (β = .48, p < .001), and social withdrawal (β = .27, p < .001). Both fears significantly predicted social withdrawal (FNE: β = .45, p < .001; FPE: β = .38, p < .001). Indirect effects of parental overcontrol on social withdrawal via FNE (B = 0.19, p < .001) and FPE (B = 0.14, p < .001) were also significant.Conclusion: These findings highlight that fear of evaluation—both negative and positive—serves as a psychological mechanism linking parental overcontrol to social withdrawal in adolescents, emphasizing the importance of addressing cognitive-affective vulnerabilities in preventive and therapeutic interventions.